On the momentum of pseudostable populations - Gustav Feichtinger; Roland Rau; Andreas J. Novak (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2023)
In a pathbreaking paper Keyfitz (1971) calculated the demographic momentum, i.e. the amount of further population growth if an immediate reduction of fertility to bare replacement would occur. While he assumes a stable initial population, our research aims to extend it to so-called pseudostable populations where fertility declines at a constant rate while mortality remains fixed. We were able to analytically obtain interesting insights into the momentum of growth of such populations. Comparing theoretical results in a pseudostable setting with the projections according to the component method showed a fit that was un-expectedly remarkably good. A peculiar effect of pseudostability is the monotonous decline of the momentum over time. Starting from a certain fixed level in the remote p ast, the m omentum c onverges to zero for an infinite time horizon. Interestingly enough, there is a time where there is neither a positive nor a negative momentum. To put it numerically, a remarkable asymmetry in the momentum is revealed. While an immediate fertility change may lead to a maximal increase of the population by a factor between 2 and 3, the maximal decrease runs up to 100%.
Keywords: 300